Identification and gene expression analysis of mating type (MAT) 1-1-1 gene in Fusarium oxysporum f.sp. cubense Tropical Race 4 - Ang, Shin Huey; Ong, Jia Xin; Terhem, Razak; Yusof, Mohd Termizi; Wong, Mui Yun; Arie, Tsutomu; Saidi, Noor Baity (University of Malaya, 2025)
Fusarium oxysporum f.sp. cubense Tropical Race 4 (Foc TR4) is a soil-borne fungal pathogen that impacts banana production. It is a member of the F. oxysporum species complex (FOSC), whose members are predominantly asexual. However, the FOSC members, including Foc TR4, retain mating type (MAT) loci, suggesting functions that are different from mating. This study identified and characterized the MAT1-1 locus in Foc TR4 and the expression of MAT1-1-1, the key gene in the MAT1-1 locus, during its interaction with susceptible bananas in vitro. The open reading frame of the identified MAT1-1-1 perfectly matched the reference sequence, and the corresponding MAT1-1-1 protein (367 amino acids) was predicted to localize to the nucleus, which matches its previously reported function as a transcriptional regulator. Based on the phylogenetic analysis of MAT1-1-1 protein sequences, Foc TR4 was grouped closely with other F. oxysporum formae speciales and clearly separated from other Fusarium species. The expression level of MAT1-1-1 was negligible in the absence of the host but was significantly induced when the host was present within a close range (at 2cm away) and at four to eight hours after being exposed to the host. These data reveal that the MAT1-1-1 of Foc TR4 is possibly associated with host sensing, allowing the pathogen to recognize specific signals from the host and activating genes required for directed hyphal growth and colonization. Overall, this study sheds light on the other potential roles of MAT genes, particularly MAT1-1-1 in Foc TR4.